Teacher Efforts to Improve Activity Study Student through Puzzle Media in Learning IPS Di Class IV SDN Siumbatu Subdistrict Bahodopi Regency Morowali - Nurhuni, Nurhuni; Hasan, Hasan; Misnah, Misnah (Journal of Education Method and Learning Strategy, 2024)
Education is a very important activity that must be applied in life man. Education is basic capital from somebody for develop potency in himself useful​ for interest his life. Problem Formulation What there is enhancement liveliness Study student through How to use puzzle media in social studies learning in class IV at SDN Siumbatu implementation How to use puzzle media in social studies learning in class IV at SDN Siumbatu liveliness Study after using puzzle media in social studies learning in Class IV SDN Siumbatu. Research purposes there is enhancement liveliness Study student through Use of puzzle media in social studies learning in class IV SDN Siumbatu. Research methods used by researchers​ namely qualitative descriptive research method. The descriptive method is a method of researching the status of a group of people, an object, a set of conditions, a system of thought or a class of events in the present (Sugiyono: 2019). Mention that the aim of this qualitative descriptive research is to obtain an overview, description of a phenomenon being studied so that accurate conclusions can be drawn. Research result Liveliness Study marked by existence involvement optimally, fine intellectual, emotional, and physical If needed. With So, you can concluded that liveliness student in Study is activities performed​ student during the learning process with activate aspect physical nor aspect spiritually and must understood as well as developed by teachers for reach objective learning with be marked involvement in aspects intellectual, emotional, and physical.